Lactobacillus plantarum LP01, Lactobacillus lactis subspecies cremoris LLC02, and Lactobacillus delbrueckii LDD01) in patients undergoing bowel preparation - Bonavina, Luigi; Ariani, Andrea; Ficano, Leonardo; Iannuzziello, Domenico; Pasquale, Luigi; Aragona, Salvo Emanuele; Drago, Lorenzo; Ciprandi, Giorgio; on digestive disorders, Italian Study Group (Acta Biomedica Atenei Parmensis, 2019)
Bowel preparation (BP) for colonoscopy induces significantly changes in gut microbiota and elicit intestinal symptoms. Impaired microbiota causes an intestinal dysbiosis. Consequently, probiotics may counterbalance the disturbed microbiota after BP. The current survey evaluated the efficacy and safety of Abincol®, an oral nutraceutical containing a probiotic mixture with Lactobacillus plantarum LP01 (1 billion of living cells), Lactobacillus lactis subspecies cremoris LLC02 (800 millions of living cells), and Lactobacillus delbrueckii LDD01 (200 millions of living cells), in 2,979 outpatients (1,579 males and 1,400 females, mean age 56 years) undergoing BP. Patients took 1 stick/daily for 4 weeks after colonoscopy. Abincol® significantly diminished the presence and the severity of intestinal symptoms and improved stool form. In conclusion, the current survey suggests that Abincol® may be considered an effective and safe therapeutic option in the management of patients undergoing BP.